Examining perceptions of food assistance on household food security and resilience in Malawi - Margolies, Amy; Kalagho, Kenan; Kazembe, Cynthia (International Food Policy Research Institute, 2019)
Malawi is extremely vulnerable to shocks and recurrent food crises (Barrett & Headey 2014). Malawi also suffers from persistently high levels of undernutrition (DHS 2016). Humanitarian aid has played an important role in alleviating hunger during emergencies, such as those in 2015-16 and 2016-17. However, the Government of Malawi and Development partners recognize that emergency responses are not a sustainable solution. This qualitative study examines the characteristics of resilient households and perceived effects of programs to improve food security and resilience from the perspective of the beneficiaries and communities they serve.